Exploring lecturers’ perception on learning organization dimensions and demographic variables in technical and vocational colleges - Nazari, Khosrow; Lope Pihie, Zaidatol Akmaliah; Idris, Khairuddin; Basri, Ramli (Universiti Putra Malaysia Press, 2014)

(untitled)
The purpose of this study was to explore the perception of 295 lecturers on learning organization dimensions and demographic variables in technical and vocational colleges in four provinces of Fars, Khuzestan, Boushehr, and Kohgilouyeh and Boyerahmad in Iran. Data was collected using a questionnaire and analyzed utilizing SPSS which included the use of descriptive and inferential statistics. The findings showed that respondents’ perceptions were rated from moderate to high in learning organization dimensions with significant differences based on the type of employment, academic rank and education level. No significant differences were observed in gender and marital status towards learning organization dimensions. The relevant literature shows few studies regarding learning organization dimensions and demographic variables locally and internationally. Therefore, the findings can be evaluated as useful information and guidance for educational administrators and leaders in utilizing learning organization dimensions in the management of educational institutions.